Slouching Toward Open Innovation: Free and Open Source Software for Electronic Health Information - Greg R. Vetter (Washington University Journal of Law & Policy, 2009)
This Article argues that some software markets are more favorable for open source approaches than others. Using a case study of one particular software market, this Article develops a tentative framework of factors characterizing markets likely to disfavor contemporary approaches in free and open source software.
Keywords: Open source software; Electronic medical records; Electronic records; Medical records; Royalties (Intellectual property); Software licensing; United States